Saving Lives: Working across Agencies and Individuals to Reduce Intimate Homicide among those at Greatest Risk - Bonomi, Amy (Journal of family violence, 2021)
This special issue of the Journal of Family Violence offers insights on intimate homicide prevention from leading researchers and practitioners. The insights offered are timely, given the pervasiveness of domestic violence (DV), including some data since the emergence of COVID-19 noting an increase in DV-related cases with severe injury and police calls. Contributors in this special issue argue for interagency advocacy, protection orders, and firearm removal, along with reimagining data capture, risk assessment, firearm protocols, and fatality reviews to improve equitable services and care for DV survivors at the highest risk of homicide.